Serum Makorin ring finger protein 3 values for predicting Central precocious puberty in girls. (3rd August 2019) - Jeong, Hwal Rim; Lee, Hye Jin; Shim, Yeong Suk; Kang, Min Jae; Yang, Seung; Hwang, Il Tae
Abstract: This study evaluated the serum level of MKRN3 and investigated its diagnostic usefulness in girls with central precocious puberty (CPP). In total, 41 girls with CPP and 35 age-matched normal control girls were enrolled. Serum values of MKRN3 were measured in both groups. Gonadotropin and estradiol concentrations were evaluated after 6 and 12 months of GnRH agonist (GnRHa) treatment in CPP patients. The MKRN3 concentrations were much lower in the patient group than in the control group ( p = .005). Over 1 year of GnRHa treatment in patients, the gonadotropin concentrations were significantly decreased ( p < .05), while the MKRN3 concentrations were unchanged ( p > .05). MKRN3 levels were inversely correlated to standard deviation (SD) in height ( r = −0.46, p = .000), SD in weight ( r = −0.32, p = .005), Tanner stage ( r = −0.41, p = .000), and bone age ( r = −0.46, p = .000). Based on ROC analysis, the area under curve was 0.758 for MKRN3, with 82.9% sensitivity and 68.5% specificity. The measurement of serum MKRN3 level may provide some help for CPP prediction, but relatively various values need further validation